Dimorphism and haploid fruiting in Cryptococcus neoformans: association with the alpha-mating type. - Wickes, B L (1996)
Cryptococcus neoformans is a major opportunistic fungal pathogen in AIDS and other immunosuppressed patients. We have shown that wild-type haploid C. neoformans can develop an extensive hyphal phase under appropriate conditions. Hyphae produced under these conditions are monokaryotic, possess unfused clamp connections, and develop basidia with viable basidiospores. The ability to undergo this transition is determined by the presence of the alpha-mating type locus and is independent of serotype. The association of the hyphal phase with the alpha-mating type may explain the preponderance of this mating type in the environment and the nature of the infectious propagule of C. neoformans.